HUBUNGAN BODY IMAGE DENGAN HARGA DIRI PADA REMAJA PUTRI USIA 16-18 TAHUN - Nia Agustiningsih; Faizatur Rohmi; Yulis Eka Rahayu (coba, 2020)
Introduvtion:Body image is an individual's attitude towards shape, appearance, and body size. Body image affects teenagers, especially young women. They tend to have a negative body image and become a reason for their low self-esteem. The purpose of this study is to find out whether there is a relationship between body image and self-esteem in young women aged 16-18 years in SMA Nasional Kota Malang. Method: Type of correlational research with cross sectional approach. The population of this research was 100 female students in the X-XI class, with a sample of 80 female students with a simple random sampling technique. The measuring instrument used for body image variables is the Multidimensional Body Self Relation Questionnaire-Appearance Scales questionnaire, and the self-esteem variable using the Rosenberg Self-Esteem questionnaire. The research was conducted at SMA Nasional Kota Malang. Data analysis using Spearman Rank, presentation of data in the form of frequency table and narration. Result:The results showed that girls aged 16-18 years in SMA Nasional Kota Malang had a positive body image of 63 (79%) and high self-esteem 41 (51.2%).The statistical test results obtained p value = 0.001 (p <0.05) so that H1 is accepted, so there is a relationship between body image and self-esteem in girls aged 16-18 years in SMA Nasional Kota Malang. Discussion:Body image in adolescents needs to be considered because the perception of body image that is less precise will be related to self-defense in adolescents. In this regard, a good support system is needed in adolescents such as families (parents) as an environment that is close to adolescents..